Evaluating physiological responses and forward head-neck posture in primary students in Thailand when carrying modified and traditional backpacks - Jittaporn Mongkonkansai; Udomsak Narkkul; Chadapa Rungruangbaiyok; Chuchard Punsawad (PLoS ONE, 2026)
Carrying backpacks daily imposes a physical burden on school-aged children, raising increasing public concern. This study compared the physiological responses and head–neck posture of primary school students when carrying traditional versus modified bags. Thirty-two public primary school students aged 7–12 years participated. Physiological measures included heart rate (HR), oxygen saturation (SpO₂), blood pressure, and respiratory rate (RR). Head and neck tilt angles and forward head posture were assessed using photogrammetry and Kinovea software. Participants walked at a natural pace (1.1–1.3 m/s) along an 8-meter walkway for five minutes under five conditions: no bag, bilateral traditional bag, unilateral traditional bag, bilateral modified bag, and unilateral modified bag. Backpack design showed significant main effects on heart rate ( p = 0.001, ηp² = 0.316), respiratory rate ( p = 0.007, ηp² = 0.214), systolic blood pressure ( p < 0.001, ηp² = 0.387), and diastolic blood pressure ( p = 0.002, ηp² = 0.279), with higher values in the traditional condition (e.g., HR 95.94 ± 2.26 bpm; RR 31.59 ± 0.86 breaths/min; systolic 108.33 ± 1.30 mmHg; diastolic 78.05 ± 1.64 mmHg). Carrying method affected HR ( p = 0.014, ηp² = 0.178), with higher values during unilateral use. No interaction effects were found for physiological variables ( p > 0.05). SpO₂ remained stable (98.78–99.47%). For posture, significant effects of design were observed for neck tilt ( p < 0.001, ηp² = 0.350), head tilt ( p = 0.001, ηp² = 0.324), and forward head posture ( p < 0.001, ηp² = 0.335). The traditional backpack produced smaller neck tilt (49.75° ± 1.05°) but greater head tilt (78.60° ± 1.56°) and forward head posture (8.68 ± 4.59 cm). Unilateral carrying increased head tilt (77.83° ± 1.56°, p = 0.021). Interaction effects were found for neck and head tilt ( p < 0.05). The modified backpack reduces physiological strain and improves postural alignment, particularly under unilateral carrying, while bilateral use minimizes asymmetrical loading.